2017
DOI: 10.1002/alr.21920
|View full text |Cite
|
Sign up to set email alerts
|

Perceived compliance and barriers to care in sublingual immunotherapy

Abstract: The majority of aqueous SLIT patients perceived their compliance to be excellent, although, based on a previous study, these patients did not reach excellent compliance benchmarks. Inconvenience of clinic visits and cost of therapy were found to be the most common barriers to care. Despite what providers perceived as less-than-excellent compliance, 82% of patients reported symptom improvement with SLIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…8 Common reasons for SLIT discontinuation included cost, improvement of symptoms without treatment, perceived lack of effectiveness, and inconvenience. 7,9 In regard to cost, aqueous SLIT is typically not covered by health insurance plans in the United States (U.S.). 10,11 In contrast, the cost of SCIT is largely dependent on the patient's insurance plan.…”
Section: Introductionmentioning
confidence: 99%
“…8 Common reasons for SLIT discontinuation included cost, improvement of symptoms without treatment, perceived lack of effectiveness, and inconvenience. 7,9 In regard to cost, aqueous SLIT is typically not covered by health insurance plans in the United States (U.S.). 10,11 In contrast, the cost of SCIT is largely dependent on the patient's insurance plan.…”
Section: Introductionmentioning
confidence: 99%
“…This Nrf2 antioxidant pathway has been shown to reduce allergic asthma in a mice model and now, for the first time has been shown to have similar effect in an allergic rhinitis model. A retrospective study by Kumar et al . of aqueous sublingual immunotherapy revealed that patients perceived their treatment compliance to be excellent even when their providers did not consider their compliance to be excellent.…”
mentioning
confidence: 99%